Single-Cell Technologies to Understand the Mechanisms of Cellular Adaptation in Chemostats - Wright, Naia Risager; Rønnest, Nanna Petersen; Sonnenschein, Nikolaus (Frontiers in Bioengineering and Biotechnology, 2020)
There is a growing interest in continuous manufacturing within the bioprocessing community. In this context, the chemostat process is an important unit operation. The current application of chemostat processes in industry is limited although many high yielding processes are reported in literature. In order to reach the full potential of the chemostat in continuous manufacture, the output should be constant. However, adaptation is often observed resulting in changed productivities over time. The observed adaptation can be coupled to the selective pressure of the nutrient-limited environment in the chemostat. We argue that population heterogeneity should be taken into account when studying adaptation in the chemostat. We propose to investigate adaptation at the single-cell level and discuss the potential of different single-cell technologies, which could be used to increase the understanding of the phenomena. Currently, none of the discussed single-cell technologies fulfil all our criteria but in combination they may reveal important information, which can be used to understand and potentially control the adaptation.